Effects of tizanidine and clonidine on postoperative pain after lumbar fusion surgery - Goli Aezi; Misagh Shafizad; Abolfazl Firouzian; Ali Mirani; Farshad Hassanzadeh Kiabi, Associate Professor of Anesthesiology (Interdisciplinary Neurosurgery, 2023)
Objectives: Postoperative pain following lumbar fusion surgery is commonly reported and is associated with significant morbidity and increased use of opioids. The aim of this study is to evaluate the effects of clonidine and tizanidine on postoperative pain in patients undergoing lumbar fusion surgery. Methods: In this double-blinded randomized study, patients referred to (XXX) for lumbar fusion surgery with ASA class I and II were included. Prior to surgery, patients were divided into three groups. Group A received one 4 mg tizanidine tablet, group B received 4 mg clonidine and group C received a placebo. After the surgery, along with demographic data, postoperative pain on a visual analogue scale (VAS), the amount of analgesic drugs required, and side effects were recorded. The data from the three groups were statistically compared using SPSS v24. Results: A total of 75 patients were studied, and were divided equally into three groups. The postoperative pain was statistically different among the three groups at 2nd and 4th postoperative hours, p = 0.002 and p = 0.018, respectively. At 6, 12, 24 and 48 postoperative hours, VAS did not differ in the two groups, p > 0.05. Furthermore, the incidence of dizziness, nausea and vomiting, drowsiness, headache, and bradycardia were not significantly different among the three groups, p > 0.05. Conclusions: The use of tizanidine and clonidine is likely to reduce early postoperative pain. However, may not affect the severity of pain a day or two after the surgery. Further studies at different doses are required to confirm these findings.